Oceanic Economic Resilience Policy: An Islamic Perspective for Coastal Sustainability - Ahmad Shukor, Ahmad Shaifful Anuar; Aldizar, Addys; Alhazami, Lutfi; Mareta, Sigit (Jurnal Lemhannas RI, 2024)
Purpose: This study analyses the application of Maqasid Syariah principles in maritime economic policies to promote social justice and sustainability in the coastal regions of Malaysia and Indonesia. It highlights key challenges and proposes Islamic-based solutions to enhance the resilience and prosperity of these areas. Study Design/Methodology/Approach:A descriptive-analytical approach was adopted, integrating Maqasid Syariah principles with the concept of national resilience. The study utilised data from literature reviews, policy analyses, and comparative studies of maritime economic frameworks in both countries to develop a comprehensive evaluation model. Findings: The findings indicate that the application of Maqasid Syariah principles strengthens sustainable development through environmental protection, equitable resource distribution, and community empowerment. However, challenges such as weak law enforcement, limited public awareness, and unequal access to resources impede effective implementation. Islamic economic instruments like zakat and waqf provide practical, inclusive solutions to these issues, with significant potential for wider application in maritime economic policies. Originality/Value: This study bridges the gap between Islamic values and modern economic policy, offering a distinctive framework for sustainable development in coastal regions. By integrating Maqasid Syariah principles, the study presents a novel strategy to tackle environmental and socio-economic challenges, thereby enhancing national resilience and sustainable growth